2020
DOI: 10.3390/ijms21051577
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction Accuracy of Seven Breeding Selection Traits Improved by QTL Identification in Flax

Abstract: Molecular markers are one of the major factors affecting genomic prediction accuracy and the cost of genomic selection (GS). Previous studies have indicated that the use of quantitative trait loci (QTL) as markers in GS significantly increases prediction accuracy compared with genome-wide random single nucleotide polymorphism (SNP) markers. To optimize the selection of QTL markers in GS, a set of 260 lines from bi-parental populations with 17,277 genome-wide SNPs were used to evaluate the prediction accuracy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
(91 reference statements)
2
16
1
1
Order By: Relevance
“…Although some of the QTNs identi ed in the present study were characterized as having a small effect, these may prove useful for genomic selection (GS) (He et al 2019a). In GS models, instead of using a complete panel of randomized SNPs, the use of markers associated with traits of interest may decrease the number of markers and, consequently, the costs of genotyping large breeding populations (Lan et al 2020). Moreover, the use of speci c trait-associated markers in GS models can improve prediction accuracy by reducing background noise in model construction (He et al 2019b;Ali et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the QTNs identi ed in the present study were characterized as having a small effect, these may prove useful for genomic selection (GS) (He et al 2019a). In GS models, instead of using a complete panel of randomized SNPs, the use of markers associated with traits of interest may decrease the number of markers and, consequently, the costs of genotyping large breeding populations (Lan et al 2020). Moreover, the use of speci c trait-associated markers in GS models can improve prediction accuracy by reducing background noise in model construction (He et al 2019b;Ali et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…GS could be more robust by integrating biological knowledge. The inclusion of QTL markers associated with the trait of interest could increase the robustness of genetic evaluation ( Ozimati et al, 2018 ; Lan et al, 2020 ). Other variables affecting the precision of the prediction model include the size of the training population, the number of markers used in the model, the trait genetic architecture, and heritability ( de Oliveira et al, 2012 ; Ly et al, 2013 ; Wolfe et al, 2017 ; Somo et al, 2020 ).…”
Section: Genomic Selection and It’s Potential In Cassava Breedingmentioning
confidence: 99%
“…In the context of animal breeding, some authors suggest that the haplotype approach may be especially beneficial for predicting traits of relatively high heritability [205,212,213]. However, in plants, prediction based on haplotypes has been especially beneficial for predicting low-heritability traits [31,33,34]. For example, Matias et al (2017) [31] reported that the predictive accuracy of the models based on haplotypes was higher than the accuracy based on SNPs (not grouped into haplotypes) at predicting the yield of corn grains, but this result was not observed in the genomic prediction of plant height.…”
Section: The Detection Of Alleles In Narrow Ld Allows the Optimization Of The Accuracy Of Genomic Prediction Modelsmentioning
confidence: 99%
“…According to Edwards (2015) [27], haplotypes can establish more precise and reliable genealogical relationships than a relationship matrix made purely from SNPs because they allow us to examine the identity by descent that exists among the individuals of a population. Interestingly, haplotypes have been used in GS models, covering extensive regions of the genome of some annual plants (such as wheat and maize), which has increased the predictive power of complex phenotypic traits [30][31][32][33][34]. Interestingly, the haplotype approach can be especially beneficial for predicting traits with a relatively low heritability.…”
Section: Introductionmentioning
confidence: 99%